The content of heavy metals in soils and plants around the waste landfill in Siechnice (Poland) - Borowczak Maciej; Hołtra Anna (E3S Web of Conferences, 2017)
Metal concentrations (Cu, Zn, Pb, Ni, Cr) in soils and plants around the metallurgical waste landfill of Siechnice, Poland, have been determined. The soil samples were collected from the surface layer of 0-25 cm. The soils and plants were digested in HNO3, 60%, using the Microwave Digestion System (Milestone Start D). The analysis of metals has been carried out through the Flame Atomic Absorption Spectroscopy (FAAS) method. The pH and the conductivity of the soil solutions were measured. The pollution index (Wn) and the bioaccumulation coefficient (WB) have been determined. The permissible content of Cu, Zn, Ni and Cr in soils were exceeded compared to the geochemical background in uncontaminated soils of Poland. Chromium concentrations have also been exceeded relative to the standard for soils, according to the Polish Ministry of Environment Regulation from September 1st, 2016. The assessment of the bioaccumulation coefficients of metals in plants (Plantagolanceolata L. and Zea mays L.) has shown significant bioaccumulation of copper and zinc compared to the permissible concentrations of undesirable substances in feed in agreement with the Polish Ministry of Agriculture and Rural Development Regulation from January 23rd, 2007.